2020
DOI: 10.2174/1570159x18666200729100427
|View full text |Cite
|
Sign up to set email alerts
|

Targeting S100B Protein as a Surrogate Biomarker and its Role in Various Neurological Disorders

Abstract: : Neurological disorders (ND) are the central nervous system (CNS) related complications originated by enhanced oxidative stress, mitochondrial failure and overexpression of proteins like S100B. S100B is a helix-loop-helix protein with calcium-binding domain associated to various neurological disorders through activation of MAPK pathway, increased NFkB expression results in cell survival, proliferation and gene up-regulation. S100B protein plays a crucial role in Alzheimer’s disease, Parkinson’s disease, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 105 publications
(119 reference statements)
0
21
0
Order By: Relevance
“…The S100b protein plays a crucial role in Alzheimer's disease, Parkinson's disease, multiple sclerosis, and epilepsy because high expression of this protein directly targets astrocytes and promotes neuroinflammation. Increased levels of S100b are useful for assessing the release of inflammatory markers, and excitotoxicity‐dependent neuronal loss (Langeh & Singh, 2021). Immunohistochemistry of the sciatic nerve showed there were numerous Iba‐1, S100b, and TLR4‐positive cells in the CCI model group while kaempferol treatment group distinctly reduced the numbers of these positive cells (Figure 2B,C).…”
Section: Discussionmentioning
confidence: 99%
“…The S100b protein plays a crucial role in Alzheimer's disease, Parkinson's disease, multiple sclerosis, and epilepsy because high expression of this protein directly targets astrocytes and promotes neuroinflammation. Increased levels of S100b are useful for assessing the release of inflammatory markers, and excitotoxicity‐dependent neuronal loss (Langeh & Singh, 2021). Immunohistochemistry of the sciatic nerve showed there were numerous Iba‐1, S100b, and TLR4‐positive cells in the CCI model group while kaempferol treatment group distinctly reduced the numbers of these positive cells (Figure 2B,C).…”
Section: Discussionmentioning
confidence: 99%
“…27 Liu et al, 58 reported neurotoxicity as a result of S100B overexpression. Also, studies have revealed that serum level of S100B could be a dependable biomarker in prediction and prognosis of cerebral infraction 59,60 .Therefore, S100B has a vital role as a biomarker for brain damage, which could result in psychiatric disorders, substance abuse as well as structural brain damage 61,62 Brain derived neurotrophic factor (BDNF) has a role in the pathology of neurodegenerative disorders. 63 In the current work administration of the examined drug at the three dosage levels caused a significant decline in BDNF mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is produced in higher quantities and released in the CSF, blood, urine, saliva, and amniotic fluid when neurons are being affected. Although it is involved in a wide spectrum of diseases (acute cerebral lesions, neurodegenerative conditions, congenital/perinatal disorders, mental disorders, meningitis), which makes it less specific, measuring it can provide useful clues during patient monitoring [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%